Cellulolytic bacteria as biocontrol agents of chili basal stem rot disease caused by Phytophthora capsici - FARHANTYO FAUZAN DWINUGROHO; GIYANTO GIYANTO; EFI TODING TONDOK; ABDJAD ASIH NAWANGSIH (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Dwinugroho FF, Giyanto, Tondok ET, Nawangsih AA. 2026. Cellulolytic bacteria as biocontrol agents of chili basal stem rot disease caused by Phytophthora capsici. Biodiversitas 27 (1): d270109. https://doi.org/10.13057/biodiv/d270109. Phytophthora capsici is a major pathogen that causes severe yield losses in chili cultivation. Its cellulose-rich cell wall presents an opportunity for biocontrol using cellulolytic bacteria capable of degrading cellulose. This study aimed to isolate cellulolytic bacteria with antagonistic activity against P. capsici and to evaluate their effectiveness in managing basal stem rot in chili. A total of 279 bacterial isolates were collected from diverse natural sources, of which 72 exhibited cellulolytic activity, with cellulolytic indices ranging from 0.22 to 10.42. Pathogenicity screening through hypersensitivity and hemolysis assays identified 26 non-pathogenic isolates. These isolates inhibited P. capsici growth by 8.15 to 79.81%. Selection of promising isolates was conducted using the Analytical Hierarchy Process (AHP), which considered both inhibition rate and plant growth-promoting traits (volatile organic compound [VOC] production, phosphate solubilization, nitrogen fixation, indole-3-acetic acid [IAA] production, and siderophore production. Based on this evaluation, five isolates were selected: S55, S61, K15, S80, and FS28, with inhibition rates of 79.81, 69.26, 57.78, 46.85, and 40.37%, respectively. In vivo greenhouse assays showed that S55 and K15 provided the highest plant survival rates (86.67 and 75.56%, respectively), compared to 50% in the control. Molecular identification revealed that S55 and S61 were closely related to Pseudomonas aeruginosa, K15 to Proteus penneri, FS28 to Bacillus altitudinis, and S80 to Brevundimonas sp. These findings demonstrate the potential of cellulolytic bacteria as biocontrol agents against P. capsici, while also highlighting the functional diversity of isolates with plant growth-promoting traits. This diversity expands the pool of candidates for sustainable and targeted disease management strategies in chili cultivation.